Generation and preclinical evaluation of a human heavy-chain-only antibody recognizing the membrane-bound tumor-associated antigen mesothelin - Janssens, Rick; van Haperen, Rien; van der Reijden, Michael; Maas, Alex; Wang, Jingsong; Grosveld, Frank; Drabek, Dubravka (Frontiers in Chemical Biology, 2024)
Objective Mesothelin (MSLN) is an attractive target for anticancer therapeutics and bioimaging reagents that utilize antibodies. This study was aimed at developing a novel human anti-MSLN single-domain antibody that exclusively binds to the membrane-attached MSLN using transgenic mice generating human heavy-chain-only antibodies (HCAbs) and exploring the resulting HCAbs as imaging tools. Methods We introduced a doxycycline-inducible human MSLN gene in genetically modified mice expressing human HCAbs. This new method of non-invasive immunization by antigen induction results in MSLN antigen production in its native conformation on the cell surface. Screening of 2,000 HCAbs from the resulting immune library yielded numerous binders, from which we chose 19G6 as the lead antibody. This antibody was 111Indium radiolabeled and tested in a xenotransplantation tumor model with OVCAR-3 cells. Results The 19G6 antibody shows nanomolar affinity toward membrane-bound MSLN and does not recognize soluble MSLN. The human MSLN-positive tumors were visualized in an in vivo mouse model. The non-labeled antibody prevented binding when provided in excess, showing tumor specificity. Conclusion 19G6 with a human Fc is a promising tumor-cell tracer in vivo. This HCAb can also be engineered into a smaller and shorter-lived tracer (only the VH domain) or combined with other target-binding domains to form multispecific modalities for tumor immunotherapy.